THE EVOLUTION OF CRM SYSTEMS: HOW TO CHOOSE THE BEST SOLUTION FOR YOUR COMPANY - Bandeira Brasiliano, Bruno (Humanas em Perspectiva, 2026)
This article addresses the evolution of Customer Relationship Management (CRM) systems and presents an analytical framework for choosing the most suitable solution for each company’s reality. The analysis focuses on essential criteria such as cost, scalability, and ease of implementation, as well as the benefits of customizations and integrations for different sectors. Based on recent market trends and comparisons among contemporary solutions, the study proposes guidelines that assist executives and managers in conducting digital transformation. The methodology adopted involves bibliographic review, case studies, and comparative analysis of solutions indexed in academic databases from the last five years.